2020
DOI: 10.31234/osf.io/u8yah
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antecedents and consequences of COVID-19 conspiracy beliefs: a systematic review

Abstract: COVID-19 conspiracy theories emerged almost immediately after the beginning of the pandemic, and the number of believers does not appear to decline. Believing in these theories can negatively affect adherence to safety guidelines and vaccination intentions, potentially endangering the lives of many. Thus, one part in successfully fighting the pandemic is to understand the antecedents and consequences of COVID-19 conspiracy beliefs, which are here presented in a rapid review summarizing research from more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
109
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 122 publications
(264 reference statements)
10
109
0
5
Order By: Relevance
“…A recent meta‐analysis shows the prevalence of anxiety during the COVID‐19 pandemic to be almost 32% (Salari et al, 2020) based on samples from all over the world. Such feelings of threat, hopelessness, and anxiety are known to be associated with a higher tendency to endorse conspiracy beliefs (for reviews, see Douglas et al, 2019; van Prooijen & Douglas, 2017; van Prooijen & van Vugt, 2018), which may be exactly why the COVID‐19 pandemic is associated with such a proliferation of conspiracy theories regarding the origin, spread, and the potential cure of the new coronavirus (e.g., van Mulukom et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis shows the prevalence of anxiety during the COVID‐19 pandemic to be almost 32% (Salari et al, 2020) based on samples from all over the world. Such feelings of threat, hopelessness, and anxiety are known to be associated with a higher tendency to endorse conspiracy beliefs (for reviews, see Douglas et al, 2019; van Prooijen & Douglas, 2017; van Prooijen & van Vugt, 2018), which may be exactly why the COVID‐19 pandemic is associated with such a proliferation of conspiracy theories regarding the origin, spread, and the potential cure of the new coronavirus (e.g., van Mulukom et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As with all conspiracy theories, it is difficult to determine the validity of those related to COVID-19 because the putative actors work in secret [ 12 ]. Although stigmatized as paranoid by some [ 5 ], such beliefs have a surprising ability to attract adherents [ 6 ], and their influence has increasingly been observed in response to COVID-19 public health recommendations, such as vaccination and social distancing [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that both misinformation [ 19 ] and conspiracy beliefs are resistant to change [ 6 , 7 , 20 , 21 ] and that holding conspiracy beliefs related to COVID-19 is associated with lower levels of behaviors known to prevent its spread [ 13 , 22 ]. In addition, single cross-sectional studies have found a positive relationship between social media use and COVID-19 misinformation [ 1 ] and conspiracy beliefs [ 14 , 23 , 24 ] and found that mainstream media consumption is associated with greater rejection of them [ 25 , 26 ]. However, such cross-sectional data cannot determine whether persistent use of these sources is related to change in these beliefs across time or whether efforts undertaken between the two surveys by media outlets to decrease the amount of conspiracy content about COVID-19–related topics is associated with a decrease in these beliefs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations